2000
DOI: 10.1016/s0014-5793(00)01141-8
|View full text |Cite
|
Sign up to set email alerts
|

High‐molecular‐weight kininogen is a binding protein for tissue prokallikrein

Abstract: Human tissue prokallikrein, a zymogen of the kallikrein-kinin system, circulates in plasma bound to neutrophils. Because plasma kininogens contribute to the assembly of kinin-generating components on blood cells, these proteins were assessed for their ability to complex the kallikrein precursor. Using ligand blot and direct binding assays, biotinylated prokallikrein was found to bind only to high-molecular-weight kininogen and not to the low-molecular-weight form. The interaction was specific, reversible, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Other components of the kinin cascade, such as the kininogens and plasma prekallikrein, were also found to localize in the neutrophil cell membrane Henderson et al, 1994). Ligand blot assays suggest that pro-hK1 may attach to the cell membrane by interacting with high-molecular-weight kininogen, but not to its low-molecularweight form Raab and Kemme, 2000).…”
Section: Inflammation and Neutrophil Functionmentioning
confidence: 99%
“…Other components of the kinin cascade, such as the kininogens and plasma prekallikrein, were also found to localize in the neutrophil cell membrane Henderson et al, 1994). Ligand blot assays suggest that pro-hK1 may attach to the cell membrane by interacting with high-molecular-weight kininogen, but not to its low-molecularweight form Raab and Kemme, 2000).…”
Section: Inflammation and Neutrophil Functionmentioning
confidence: 99%
“…Similarly, Kemme et al [17] have shown that tissue prokallikrein localizes bound to the neutrophil surface in addition to the intracellular compartment. Ligand blot assays suggest that tissue prokallikrein may attach to the cell membrane also by interacting with H-kininogen [18]. In addition, binding experiments using purified cell membranes have shown that neutrophils display kinin-binding sites that have been characterized as B1 and B2 kinin receptor subtypes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nonspecific binding was subtracted from total HK binding, and binding affinity was calculated using Scatchard analysis. To determine the dependence of Ft/HK binding on the presence of zinc, 10 M ZnCl2 was added to each well along with biotinylated HK (38).…”
Section: Methodsmentioning
confidence: 99%